Factors Affecting Chicken Livestock Business Income in Lubuk Linggau City - Dita Melandari; Aris Munandar; Vhika Meiriasari (International Journal of Community Service & Engagement, 2022)
This research aims to analyze the amount of independent chicken business income and the factors that affect the income of independent chicken farming. This study analyzed 5 independent chicken breeders in Lubuk Linggau City which is a chicken production center. The data was collected by the survey method and analyzed using multiple linear regression. The findings of this research identified that the amount of chicken ownership, education, labor, production costs, and selling price had a positive effect on the income of independent chicken breeders in Lubuk Linggau City. While farmers' age and experience did not have a positive effect on their income. The results show the correlation coefficient test (R) obtained a value of 0.82, which means the relationship between independent variables and income is 82.1% and the rest is influenced by other variables not included in this study. This research is useful for independent chicken breeders to consider the amount of chicken ownership, education, labor, production costs, and selling price because they have a positive effect on income.